Pengaruh Agresivitas Pajak Terhadap Nilai Perusahaan Dengan Tata Kelola Perusahaan Sebagai Variabel Moderasi - Laksmitasari Azizah, Nurifa (LP2M Politeknik Jambi, 2023)
The point of this exploration is to see if charge forcefulness affects organization esteem. Aside from that, this exploration likewise tests whether corporate administration components impact the connection between charge forcefulness and firm worth. Looking at the directing impact of corporate administration on the connection between charge forcefulness and firm worth in the Indonesian setting is still seldom finished. Utilizing 213 organization year tests from 2018-2022 information from 76 public organizations recorded on the IDX from the purchaser cycle area, this examination relapses (1) charge forcefulness on firm worth, (2) the association between charge forcefulness and corporate administration on firm worth. mark. The experimental outcomes give proof that charge forcefulness adversely affects organization esteem. Nonetheless, this exploration doesn't give experimental proof that the impact of duty forcefulness on organization worth can be directed by corporate administration instruments